2019
DOI: 10.1038/s41598-019-46065-3
|View full text |Cite
|
Sign up to set email alerts
|

A Biochar-Based Route for Environmentally Friendly Controlled Release of Nitrogen: Urea-Loaded Biochar and Bentonite Composite

Abstract: Biochar-based fertilizers have attracted increased attention, because biochar can improve the soil fertility, promote plant growth and crop yield. However, biochar-based controlled release nitrogen fertilizers (BCRNFs) still face problems because of the high cost, inefficient production technology, instability of nitrides, and the challenge associated with the controlled release of nutrients. In this study, we hydrothermally synthesised novel BCRNFs using urea-loaded biochar, bentonite and polyvinyl alcohol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 52 publications
8
79
0
2
Order By: Relevance
“…Even though research into BFs is still in a fledgling state, the few available studies overwhelmingly substantiate the slow release capabilities of the fertilisers with the level of efficiency of the slow release capacities heavily dependent on the preparation methods used. For example, Liu et al [15] indicated that a fertiliser produced by mixing biochar and urea through grinding slowed N release by less than 10% in the first 28 days of the experiment while formulating the same mixture under a sealed reactor led to a slight increase in the slow release capacity of the resultant fertiliser. Additionally, halving the urea concentration while doubling the biochar content and adding bentonite to the mixture in the sealed reactor produced a fertiliser that released only 86.7% of N which accentuated an improvement in the slow release potential of the produced fertiliser.…”
Section: Slow Releases Of N and P From Bbfsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though research into BFs is still in a fledgling state, the few available studies overwhelmingly substantiate the slow release capabilities of the fertilisers with the level of efficiency of the slow release capacities heavily dependent on the preparation methods used. For example, Liu et al [15] indicated that a fertiliser produced by mixing biochar and urea through grinding slowed N release by less than 10% in the first 28 days of the experiment while formulating the same mixture under a sealed reactor led to a slight increase in the slow release capacity of the resultant fertiliser. Additionally, halving the urea concentration while doubling the biochar content and adding bentonite to the mixture in the sealed reactor produced a fertiliser that released only 86.7% of N which accentuated an improvement in the slow release potential of the produced fertiliser.…”
Section: Slow Releases Of N and P From Bbfsmentioning
confidence: 99%
“…The results of the Liu et al [15] experiment demonstrate therefore, that mere mixing of biochar with urea has little impact on slowing N release and that more means of improving urea absorptivity into biochar should be explored if the slow release potentials of the generated fertilisers are to be maximised. Basing on that line of thought, it's surprising that mere soaking of biochar in UHP solutions undertaken in the current study produced more efficient slow release N fertilisers than the hydrothermal decomposition route espoused by Liu et al [15].…”
Section: Slow Releases Of N and P From Bbfsmentioning
confidence: 99%
See 2 more Smart Citations
“…Release of the nutrients adsorbed by biochar could be the reason of a higher dry biomass yield in EB treatment. For example, Liu et al (2019) in their experiment with urea-enriched biochar found a 61-98% release of nitrogen from biochar to the soil through dissolution and diffusion processes.…”
Section: Nutrients Uptake From Biocharmentioning
confidence: 99%